Trend 2010 - 2012. Statistics Canada. CANSIM: Travel and Tourism - Domestic Travel | Country: Canada | Province: Nunavut | Table: Air passenger traffic and flights | Variable: Domestic sector | Units: #, 2010-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-199. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Travel and Tourism - Domestic Travel | Country: Canada | Province: Nunavut | Table: Air passenger traffic and flights | Variable: Domestic sector | Units: #, 2010-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-199. Dataset: Reports statistics on socioeconomic variables related to travel by Canadian residents within Canada, such as expenditures, province of origin and destination, main purpose of trip, trip duration, activities, modes of transport used, and distance travelled. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Domestic Tourism, Domestic Tourists, Travel Industry, Tourism Industry